Impuesto diferido: evolución y procedimiento del impuesto diferido (2017)
In dealing with the issue regarding deferred tax, it is based on deepening the management of the evolution, procedures and advantages that companies obtain when applying this tax, but not only must take into account the above, another important point is the difference between the Local and international accounting standards. By going deeper into the above issues, one can identify the great role that accountants have in applying the deferred tax in companies, and in this way help to reflect the economic and financial reality of the economic entity, more now with the adoption of New accounting and financial standards that are based on the global, and are thus far from the tax rules of each country. This research study gives as a result know differentiate and compare the tax deferred from the national standard as an international standard, clarifying the inequalities that can be found by applying the tax parameters, this tax to be mandatorily under the international standards for the company's own benefit.